Budget and capabilities of information technology governance: empirical analysis in higher education institutes - Vicente Merchan-Rodríguez; Danny Zambrano-Vera (Institute of Advanced Engineering and Science, 2023)
Despite empirical improvements in Ecuador's higher institutes in preparing for information technology (IT) governance, much remains to be done to improve understanding of the maturity of governance structures, processes, and relational mechanisms with the referential budget allocated to IT departments. In this sense, the objective of the work is to analyze the maturity of the IT governance mechanisms and the referential budget allocated, from the relational and predictive point of view, going through a descriptive process. The data that was analyzed comes from the 2020 opinion survey, conducted by a group of researchers with support from the National Secretariat of Higher Education, Science, Technology, and Innovation of Ecuador (SENESCYT). In total, 18 institutes completed the survey with budget information. The findings show the considerable absence of internal processes, weak positive and negative relationship between variables; and the low level of maturity of the mechanisms of IT governance capacities, for the time being, is not significant for the institutional budget. In conclusion, this analysis can provide a baseline to assist in the preparation of action plans for institution-building. In addition, it allowed identifying several weaknesses and strengths, not only in institutions but also in research.